2021
DOI: 10.1186/s12877-021-02067-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported morbidities, nutritional characteristics, and associated factors in institutionalized and non-institutionalized older adults

Abstract: Background As the world’s population ages and people live longer, it seems important to ensure that older people have a good quality of life and positive subjective well-being. The objective of this study is to determine socio-economic, health and nutritional characteristics of institutionalized and non-institutionalized elders in the province of Marrakech. Methods This study was conducted among 368 older adults in the province of Marrakech between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Current study findings are also in accordance with a study from Egypt by Hassan et al (2017), which found that the institutionalised elderly under study experienced significant psychological problems with depression, isolation, and anxiety. The present study found physical health problems faced by the elderly were mainly related to their eyes, hearing, and dental/mouth, which are in accordance with the findings of the studies by Benksim et al (2021), Rani (2018), andAkbar (2021). The results of the current study showed that most respondents were suffering from psychological and emotional disturbances along with physical ailments of multiple natures during their stay at an old age home, and another study by Brahmbhatt and Shah (2019) found the same: the majority of elderly residing in an old age home from physical as well as psychological problems.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Current study findings are also in accordance with a study from Egypt by Hassan et al (2017), which found that the institutionalised elderly under study experienced significant psychological problems with depression, isolation, and anxiety. The present study found physical health problems faced by the elderly were mainly related to their eyes, hearing, and dental/mouth, which are in accordance with the findings of the studies by Benksim et al (2021), Rani (2018), andAkbar (2021). The results of the current study showed that most respondents were suffering from psychological and emotional disturbances along with physical ailments of multiple natures during their stay at an old age home, and another study by Brahmbhatt and Shah (2019) found the same: the majority of elderly residing in an old age home from physical as well as psychological problems.…”
Section: Discussionsupporting
confidence: 92%
“…The most crucial element of any person's life, according to the study's conclusion, is creating a financial plan for the future by the time they reach middle age. Benksim et al (2021) carried out a study that aimed to investigate the socio-economic, health, and nutritional attributes of the elderly in the province of Marrakech who were either institutionalised or not. Between March 2017 and June 2019, 368 older people participated in the study; of them, 180 lived in public institutions and 188 were housed in their own homes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation